Higher Order DiRerential Operators with Finite Number of d-Interactions in Multivariate Case - Eyvazov, E.H. (Журнал математической физики, анализа, геометрии, 2010)
A formula for calculating the defect number of a multi-center differential operator of higher order is obtained. The spectral properties of selfadjoint operators describing the finite number pointwise interactions are studied.